2010
DOI: 10.1097/ftd.0b013e3181f3c063
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Effect of CYP3A5 Genotype on the Apparent Oral Clearance of Tacrolimus in Renal Transplant Recipients

Abstract: Tacrolimus is a commonly used immunosuppressive agent in renal transplantation. Therapeutic drug monitoring of tacrolimus is recommended because it demonstrates wide pharmacokinetic interpatient variability. Part of that variability may be the result of metabolism by cytochrome P450 3A5 (CYP3A5), which is only expressed in some adult individuals. The expression of CYP3A5 has been linked to the CYP3A5 genotype, in which individuals with one or more wild-type allele (CYP3A5*1) are considered CYP3A5 expressors, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
51
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 31 publications
9
51
0
1
Order By: Relevance
“…Few studies have examined the relationship between the CYP3A5 polymorphism and tacrolimus level in liver transplant patients. Moreover, the findings from these studies are inconsistent: some results showed that the receptor genotype has important implications for the metabolism of tacrolimus (Li et al, 2013;Spierings et al, 2013;Zhang et al, 2013), while other studies showed that blood tacrolimus level is more closely associated with the donor genotype (Barry and Levine, 2010;De Jonge et al, 2012;Valente et al, 2013).…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Few studies have examined the relationship between the CYP3A5 polymorphism and tacrolimus level in liver transplant patients. Moreover, the findings from these studies are inconsistent: some results showed that the receptor genotype has important implications for the metabolism of tacrolimus (Li et al, 2013;Spierings et al, 2013;Zhang et al, 2013), while other studies showed that blood tacrolimus level is more closely associated with the donor genotype (Barry and Levine, 2010;De Jonge et al, 2012;Valente et al, 2013).…”
Section: Introductionmentioning
confidence: 70%
“…However, in liver transplantation, the contribution of donor liver and recipient gut on tacrolimus metabolism increases the complexity of the mechanism of tacrolimus metabolism. Few studies have examined the relationship between the CYP3A5 polymorphism and variation in tacrolimus individual differences following liver transplantation, and the results are controversial (Barry and Levine, 2010;Valente et al, 2013).…”
Section: Influence Of Age Time Course and Graft Liver Weight On Thementioning
confidence: 99%
“…that is metabolized three times more efficiently by CYP3A5 compared with CYP3A4 (Barry and Levine, 2010). Hence, maintaining the required minimal tacrolimus trough concentrations in patients who express CYP3A5 variants *1/*1 and *1/*3 requires approximately twice the dose compared with patients with the *3/*3 (inactive) genotype (Iwasaki, 2007).…”
Section: Discussion Cytochrome P450smentioning
confidence: 99%
“…Some CYP3A substrates are reportedly affected by the CYP3A5 genotype, such as tacrolimus (Barry and Levine, 2010), verapamil (Jin et al, 2007), vincristine (Dennison et al, 2006, 2007, Santoro et al, 2013, and cyclosporine (Zhu et al, 2011). Tacrolimus is one example which shows clinical relevance of the CYP3A5 genotype worthy of further discussion.…”
Section: Discussion Cytochrome P450smentioning
confidence: 99%
“…The last reviewed work, with 200 patients objectifies that patients who were CYP3A5*3/*3 received significantly higher tacrolimus dose at 1 week, 6 months, and 1 year (Tavira et al, 2011). Some studies found that the weighted mean apparent oral clearance was 48% lower in CYP3A5 nonexpressors than CYP3A5 expressors (range, 26%-65%) (Barry & Levine, 2010). Recently, a study with 280 transplant recipients concludes that patients receiving a pharmacogenetic adaption of the daily dose of tacrolimus were associated with improved achievement of the target C 0 (Thervet et al, 2010).…”
Section: Influence On Tacrolimus Pharmacokineticsmentioning
confidence: 99%